Incarcerated vaginal ring pessary in short duration: an uncommon complication - Ravi, Sowmiya; Mayilvahanan, Karthika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
In pelvic organ prolapse (POP), vaginal pessaries are considered as most effective, safe and highly acceptable management. This is a case report of 78-year, multiparous postmenopausal women who had vaginal pessary insertion for POP and lost follow up came to hospital after 3 months. On speculum examination it revealed a right-side vaginal wall focal ulceration of size 0.5×0.5 cm noted which bled on touch, displaced left lateral part of pessary with a 1.5cm band of tissue overgrowing it. It was managed by surgical removal under general anaesthesia and local oestrogen cream application. It is concluded that to avoid this type of complication patient education and good compliance plays a major role.